Implementing Project-Based Worksheets on Making Kaolin Soap with the Addition of Kefir Curd to develop students' scientific performance in Islamic School - Darojah, Teja Zakiah; Windayani, Neneng; Irwansyah, Ferli Septi (ASEAN Journal for Science and Engineering in Materials, 2024)
This research aims to describe student activities during the application of project-based worksheets, analyze scientific performance, and analyze the characteristics of the resulting kaolin soap with the addition of kefir curd. The research method used is pre-experimental with a one-shot case study research design. The research subjects were 34 students of XI grade in an Islamic school in Bandung, Indonesia. The results of the research show that the percentage of student activity during the application of the worksheet is 87 in the very good category. The highest average score was 94 with a very good category at the stage of carrying out the research. The students' scientific performance ability in applying worksheets reached 86 in the very good category. The highest average score is 92 with the very good category found in the indicator for interpreting data. The results of the characterization of the kaolin soap produced follow Indonesian National standard No. 3532:2021 with a pH value of 10, the foam stability values respectively from highest to lowest are 89, 85, 83, 60, and 50%. Based on the organoleptic test, the soap has a solid texture and smells like clay with a bone-white color. This shows that the implementation of project-based worksheets can be carried out well